A study of some biocontrol mechanisms of Beauveria bassiana against Rhizoctonia disease on tomato - Azadi, Narges; Shirzad, Akbar; Mohammadi, Hamid (Acta Biologica Szegediensis, 2016)
Tomato damping-off, caused by Rhizoctonia solani, is one of the most common diseases worldwide. The use of biological control agents to protect plants against pathogens seems to be an appropriate solution. Beauveria bassiana as an endophytic fungus can colonize a wide range of plants in a systemic manner and enhance plant resistance. In this study, the ability of three isolates of B. bassiana to control damping-off of tomato seedlings was examined. The effect of B. bassiana on the induced systemic resistance enzymes such as peroxidases (POX) and phenylalanine ammonia-lyase (PAL) and also the phenolic compounds content in plant resistance was measured. Our results showed that B. bassiana isolates especially TS12 and TS7 resulted in an increase in the activity of POX and PAL enzymes as well as enhanced the contents of phenolic compounds in treated plants. The results of greenhouse studies showed that each of the three isolates were able to successfully control tomato damping-off. However, this ablity was probably due to the stimulation of plant growth by KJ24, but TS12 and TS7 isolates acted through the stimulation of “induced systemic resistance” in plants.